2014
DOI: 10.1093/annhyg/met075
|View full text |Cite
|
Sign up to set email alerts
|

Collection Efficiencies of High Flow Rate Personal Respirable Samplers When Measuring Arizona Road Dust and Analysis of Quartz by X-ray Diffraction

Abstract: Prolonged exposure to respirable crystalline silica (RCS) causes silicosis and is also considered a cause of cancer. To meet emerging needs for precise measurements of RCS, from shorter sampling periods (<4h) and lower air concentrations, collaborative work was done to assess the differences between personal respirable samplers at higher flow rates. The performance of FSP10, GK2.69, and CIP 10 R samplers were compared with that of the Safety In Mines Personal Dust Sampler (SIMPEDS) sampler as a reference, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Performance of high flow rate samplers was previously investigated in laboratory experiments (Lee et al ., 2010, 2012; Stacey et al ., 2014) and the high flow rate samplers (CIP10-R, FSP10, and GK2.69) were shown to meet the performance requirement from the International Organization for Standardization (ISO) with respect to respirable convention sampling (ISO, 1995). The samplers showed <30% difference in mass concentration compared to ideal respirable fraction in accordance with a standard protocol (EN13205, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Performance of high flow rate samplers was previously investigated in laboratory experiments (Lee et al ., 2010, 2012; Stacey et al ., 2014) and the high flow rate samplers (CIP10-R, FSP10, and GK2.69) were shown to meet the performance requirement from the International Organization for Standardization (ISO) with respect to respirable convention sampling (ISO, 1995). The samplers showed <30% difference in mass concentration compared to ideal respirable fraction in accordance with a standard protocol (EN13205, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The samplers showed <30% difference in mass concentration compared to ideal respirable fraction in accordance with a standard protocol (EN13205, 2002). Averages of respirable dust mass concentration and quartz mass concentration ratios comparing high and low flow rate samplers from laboratory studies (Lee et al ., 2012; Stacey et al ., 2014) and from the present study are shown in Table 5. Although the average ratios from the laboratory studies are based on arithmetic means with standard deviations and those from the present study are GMs and upper and lower 95% confidence intervals without outliers, the average ratios from the studies are comparable in both respirable dust mass concentration and quartz mass concentration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations